30 Years of Microsurfacing: A Review. (26th April 2012) - Broughton, Ben; Lee, Soon-Jae; Kim, Yoo-Jae
Abstract : Microsurfacing has been utilized in the United States since 1980 as a maintenance treatment for pavement. This paper reviews the benefits, limitations, and factors that contribute to successful applications of microsurfacing. The history of microsurfacing, as well as a definition and process description of the treatment, is included. The body of scientific work on microsurfacing is shown to promote its use in preventative maintenance programs, and the potential for microsurfacing to meet tightening environmental and budgetary restrictions is discussed. Suggestions are given for future research to expand microsurfacing's applications and efficacy stemming from the ability of microsurfacing to be cold-applied and utilize polymers in the bitumen.